2014
DOI: 10.1177/1039856214563845
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of imminent aggression in mentally ill young offenders

Abstract: It is possible to monitor the risk state of hospitalised mentally ill youth, so that heightened states can be detected early, thus facilitating interventions to reduce the risk of violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Large suggests that risk assessment, as described in our study, 1 distracts staff from patient care, due to an excessive opportunity cost. This is incorrect.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Large suggests that risk assessment, as described in our study, 1 distracts staff from patient care, due to an excessive opportunity cost. This is incorrect.…”
mentioning
confidence: 79%
“…He is mistaken in his belief that it is not worth attempting to elucidate precursors for imminent aggression in young offenders with a mental illness. 1 There is evidence that short-term risk assessment can reduce aggression and reliance on coercive measures. Several European studies have tested the impact of risk assessments on the use of restrictive practices and aggressive behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 16 A final risk judgment (low, medium, high) is formed based on a review of the items and the total score as well as knowledge of the patient’s usual behavior and history of violence. 16 The DASA has been validated in various clinical settings, 26 , 34 , 35 both in Asia 36 and in Western countries. 30 , 33 It has repeatedly exhibited good-to-excellent predictive accuracy for aggression, 25 , 26 , 36 with good internal consistency and interrater reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Outside Stressors was added because acute stress is thought to increase aggressive behavior, especially if unable to resolve during hospitalization (Daffern & Ogloff, 2014). The youth version was tested and predicted imminent aggression (AUC = 0.754) in a prospective validation study with mentally ill adolescent male offenders in a forensic hospital setting and demonstrated improvement of predictive accuracy compared with the adult version DASA (Kasinathan et al, 2015). At the time of this study, the youth version (DASA-YV) of the adult DASA tool had yet to be validated in the youth inpatient psychiatric population.…”
Section: Introductionmentioning
confidence: 99%